2011
DOI: 10.1161/strokeaha.111.631135
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Type Gelsolin Is Decreased in Human Blood and Cerebrospinal Fluid After Subarachnoid Hemorrhage

Abstract: Background Subarachnoid hemorrhage (SAH) pathophysiology involves neurovascular proteolysis and inflammation. How these two phenomena are related remains unclear. We hypothesize that matrix metalloproteinases (MMPs) mediate the depletion of anti-inflammatory plasma-type-gelsolin (pGSN). Methods We enrolled 42 consecutive SAH subjects and sampled CSF and blood on post-SAH days 2–3, 4–5, 6–7, and 10–14. Controls subjects were 20 consecutive non-SAH hydrocephalus patients with lumbar-drains. LISA, western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…Previous research has shown pGSN to be present in the CSF compartment in SAH and that MMPs may mediate the depletion of pGSN [9,12]. Taken together, these studies suggest that, in the case of SAH, pGSN may be more than just a non-specific marker.…”
mentioning
confidence: 58%
“…Previous research has shown pGSN to be present in the CSF compartment in SAH and that MMPs may mediate the depletion of pGSN [9,12]. Taken together, these studies suggest that, in the case of SAH, pGSN may be more than just a non-specific marker.…”
mentioning
confidence: 58%
“…Detailed descriptions of biorepository methods have been previously published (3,4). SAH subjects were included if they present within 96 h of spontaneous aneurysmal or pre-pontine SAH and had hydrocephalus requiring external ventricular drain (EVD) placement.…”
Section: Methodsmentioning
confidence: 99%
“…Subarachnoid hemorrhage significantly upregulates both the expression and activity of matrix metalloproteinase-9 (MMP-9) in blood and CSF. 5961 Several different experimental models suggest that MMP-9 activity mediates blood-brain barrier breakdown and subsequent vasogenic edema following aSAH. Genetic deletion of MMP-9 both protects the integrity of the blood-brain barrier 62 and reduces edema formation 63 in mouse models of aSAH.…”
Section: Molecular Mechanismsmentioning
confidence: 99%